MASS AND COUNTABILITY IN ENGLISH NOUNS - Mohammed Basil K. Al - Azzawi (آداب الرافدين, 1982)
This paper attempts to elucidate and substantiate the points that there is a referential validity underlying nouns in English and that this validity is more apparent and consistent  in concrete than in abstract nouns;  also that abstract nouns, too, broadly follow the general patterns of concrete nouns.  The study has been made in three parts: I. A brief review of the criteria generally applied in defining English nouns.  li.  A study of the distinction between mass and count in concrete nouns employing referentiality as the basis.  iii.  A study of dual membership.  viz.  the occurrance of one noun as both count (concrete and abstract) and mass (concrete and abstract).